(untitled) (Research, Society and Development, 2020)
Milk is a food rich in nutrients and widely consumed, playing a very important role for human consumption. The occurrence of antibiotic residues in milk can cause serious risks to the health of consumers and also damage to the dairy industry. Considered as the main critical point of control of chemical contamination, the presence of antibiotic residues in milk must be observed during the reception of the raw material in the industry. The matter requires a lot of attention and has been the subject of constant concern by health authorities. Thinking about the risks to the consumer and public health, the objective of this work was to evaluate the occurrence of antibiotic residues in samples of UHT whole milk from 14 different brands under Federal Inspection marketed in the main retail establishments in the municipality of Rio Verde - GO. The samples were acquired between the months of July and August 2017 and the SNAP® Beta-Lactam ST Plus rapid test was used to perform the analyzes, according to the sensitivity of the test for the detection of antibiotic residues in the beta group. -lactamics, including cephalexin. Of the total of 40 samples analyzed, none were positive for the presence of antibiotic residues. The results obtained demonstrate the commitment of those involved in the milk production and processing chain to the safety of the food offered to consumers and to the legislation in force, which considers milk contaminated with antibiotic residues as inappropriate for human consumption.